Kebebasan dan Kebahagiaan dalam Perspektif Jhon Stuart - Haikal Ginan Musyadad; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss happiness and the freedom perspective of John Stewart. The research method used is a qualitative type through library research. The results and discussion of this research are that there are fundamental differences between freedom and happiness. Freedom is the highest value of human dignity and its commitment to find a way. liberating the poor and oppressed into coercion that continues to overshadow his life as an integrative thinker. But the pressure is precisely the tension between his obsession with freedom on the one hand and his tendency to find ways to break free on the other; lies irony and paradox. Subordinated to freedom and justice must be paramount if the path of emancipation is found. Freedom and justice, the two public virtues, are often considered as one entity.